Moslem Women: Modification Of Belle Character Costumes In Film Beauty And The Beast - Mauly Putri Dipiati; Hery Supiarza (Universitas Pendidikan Indonesia, 2021)
In modern times, clothing is not only used as a cover and self-protection but also has its trend. In Islam, the clothes used have rules between men and women. The clothes that these women wear in Islam are known as the hijab. Hijab is one type of clothing that is identical to Muslim women. The artistic modification of Belle's character clothing in Beauty and The Beast with a Muslim theme is one way to show the public that Belle's clothes in the cast are no less attractive than the costumes of the original Disney characters. The method that will be used refers to the transformation method, which is the process of changing one design that is more different than before. However, this transformation process does not leave its original form. The Muslim theme in Belle's character clothing is a style development aimed at Muslim women who wear the hijab these days. Fashion modification Muslim woman themed has the aim a renewal of Belle's character outfit. In contrast to the original, Muslim fashion models do not only cover the wearer's genitals but are intended for women to have characteristics and make women a permanent symbol of beauty by following the rules as Muslims. Fashion is all equipment, including accessories that accompany the actress or player in a film, which serves to describe the characteristics of the character played. Keywords — Moslem Women, Modification, Costume, Character